Identification of Waste in Dolomite Stone Using the Waste Assessment Model Method in the Implementation of Lean Manufacturing - Saliem, Muhammad Niqey Dzi Qolbin; Situmeang, Joumil Aidil Saifuddin Zuhri; Winursito, Yekti Condro (Journal La Multiapp, 2025)
Production plays an important role in maintaining the quality and quantity of products until they reach consumers. The many important activities in the production process require companies to improve their performance to be effective and efficient in order to maintain trust. PT XYZ is a BUMD company engaged in the manufacturing of fertilizer and dolomite rock mining materials since 2018. In production activities, there are various activities that do not have added value or waste. This study aims to identify waste and find out the root causes of waste in production process activities. The implementation of Lean manufacturing is carried out by identifying the warehousing flow process with Value Stream Mapping (VSM), then identifying 7 wastes that occur in the warehousing process using the Waste Assessment Model (WAM) method. The results of the study showed that the waste with the highest percentage level was waste Processing (P) waste transportation (T) waste overproduction (D). From the proposed improvements and mapping of future flows, it was found that lead time was reduced to 264 minutes from 350 minutes, which means eliminating 86 minutes of activities that did not provide added value. Thus, activity increased by 22% from the initial condition.